Deep inferior epigastric perforator free flap in elderly women for breast reconstruction: The experience of a tertiary referral center and a literature review. Issue 9 (13th July 2021) - Dejean, Marie F.; Dabi, Yohann; Goutard, Marion; Taveau, Corentin B.; Lantieri, Laurent A.; Lellouch, Alexandre G.
Abstract: Background: A general belief is to consider elderly patients as poor candidates for free flap reconstruction, which does not reflect our 20‐year experience for breast reconstruction (BR). The aim of this study was to determine the safety and benefits of BR using deep inferior epigastric perforator (DIEP) free flap in the elderly population. Methods: We conducted a retrospective study of all consecutive BRs using DIEP flaps in patients 65 years or older at the European Georges Pompidou Hospital from January 2011 to December 2019. Postoperative complications were reported as minor or major. We used a descriptive approach to analyze the main characteristics of the patients included. Surgical patient‐reported outcomes and quality of life were assessed using the validated BREAST‐Q questionnaire. Results: Eighty‐three DIEP flaps were performed in 79 patients (4 bilateral flaps) for BR. Sixty‐six percent of the patients (52/79) did not present any complication. Total flap loss occurred in 3 BR (3.6%), arterial thrombosis in 4 BR (4.8%), and venous thrombosis in 8 BR (9.6%). The average duration of inpatient stay was 9.5 (±2.7) days. Forty‐one of 69 eligible patients completed the questionnaire (response rate 59.4%). Patients reported high satisfaction and well‐being scores. The mean Q score for psychosocial well‐being was 75.4 (±16.7) and 59 (±13.3) for satisfaction with breasts. Conclusion: In our retrospective cohort, DIEP flap BR in elderly population had similar success and complication rates compared with those in younger patients, as well as high satisfaction scores. The free flap should be encouraged for BR in women over 65 years of age, and personal motivation as well as physiological age considered as main criteria for patient selection.